Uranium(iv) alkyl cations: synthesis, structures, comparison with thorium(iv) analogues, and the influence of arene-coordination on thermal stability and ethylene polymerization activity. Issue 46 (10th November 2022) - Andreychuk, Nicholas R.; Vidjayacoumar, Balamurugan; Price, Jeffrey S.; Kervazo, Sophie; Peeples, Craig A.; Emslie, David J. H.; Vallet, Valérie; Gomes, André S. P.; Réal, Florent; Schreckenbach, Georg; Ayers, Paul W.; Vargas-Baca, Ignacio; et al.
Abstract : Uranium(iv ) alkyl cations have been prepared, and arene solvent coordination was shown to have a major impact on ethylene polymerization activity. Actinide-arene binding was studied experimentally in the solid state and solution, and computationally. Abstract : Reaction of [(XA2 )U(CH2 SiMe3 )2 ] (1 ; XA2 = 4, 5-bis(2, 6-diisopropylanilido)-2, 7-di- tert -butyl-9, 9-dimethylxanthene) with 1 equivalent of [Ph3 C][B(C6 F5 )4 ] in arene solvents afforded the arene-coordinated uranium alkyl cations, [(XA2 )U(CH2 SiMe3 )(η n -arene)][B(C6 F5 )4 ] arene = benzene (2 ), toluene (3 ), bromobenzene (4 ) and fluorobenzene (5 ). Compounds 2, 3, and 5 were crystallographically characterized, and in all cases the arene is π-coordinated. Solution NMR studies of 2–5 suggest that the binding preferences of the [(XA2 )U(CH2 SiMe3 )] + cation follow the order: toluene ≈ benzene > bromobenzene > fluorobenzene. Compounds 2–4 generated in C6 H5 R (R = H, Me or Br, respectively) showed no polymerization activity under 1 atm of ethylene. By contrast, 5 and 5-Th (the thorium analogue of 5 ) in fluorobenzene at 20 and 70 °C achieved ethylene polymerization activities between 16 800 and 139 200 g mol −1 h −1 atm −1, highlighting the extent to which common arene solvents such as toluene can suppress ethylene polymerization activity in sterically open f-element complexes. However, activation of [(XA2 )An(CH2 SiMe3 )2 ] M = U (1 ) or Th (1-Th ) with [Ph3 C][B(C6 F5 )4 ] in n -alkane solvents did not afford an active polymerization catalyst due to catalyst decomposition, illustrating the critical role of PhX (X = H, Me, Br or F) coordination for alkyl cation stabilization. Gas phase DFT calculations, including fragment interaction calculations with energy decomposition and ETS-NOCV analysis, were carried out on the cationic portion of 2′-Th, 2′, 3′ and 5′ (analogues of 2-Th, 2, 3 and 5 with hydrogen atoms in place of ligand backbone methyl and tert -butyl groups), providing insight into the nature of actinide–arene bonding, which decreases in strength in the order 2′-Th > 2′ ≈ 3′ > 5′ .